Immunostimulatory potential and proteome profiling of Leishmania donovani soluble exogenous antigens. (July 2015) - Kumar, A.; Samant, M.; Misra, P.; Khare, P.; Sundar, S.; Garg, Ravendra; Dube, A.
Summary Isolation of the soluble exogenous antigens (SEAgs), its immune response study and proteome profiling is an essential prerequisite for understanding the molecular pathogenesis of Leishmania donovani. The immunostimulatory potential of L. donovani SEAgs, purified from culture of L. donovani clinical isolate, was evaluated for their ability to induce cellular responses in treated/cured hamsters. SEAgs induced significant proliferative responses in lymphocytes (SI 5·6 ± 2·3; P < 0·01) isolated from cured hamster. In addition, significant NO production in response to SEAgs was also noticed in macrophages of hamsters, mouse and human cell lines (J774A‐1 and THP1). Western blot analyses with antibodies against proteophosphoglycan (PPG; surface‐expressed and secreted molecule) of L. donovani revealed that PPG molecules are also present in L. donovani SEAgs. Mass spectrometry (MS)‐based proteome analysis of 12 protein bands of SEAgs through MALDI‐TOF/TOF endorsed the identification of some Th1‐stimulatory immunogenic proteins. These immunogenic proteins may offer increased hope for the discovery of new promising vaccine candidates against visceral leishmaniasis (VL). The overall results suggest that immunostimulatory molecules are present in the SEAgs, which may be further exploited, for developing a subunit vaccine against VL a fatal human disease.